An atypical manifestation of inguinal endometriosis in the extra pelvic part of the round ligament: a case report - Chiantera, Vito; Abesadze, Elene; Ibrahim, Mohamed Gamal; Dückelmann, Anna Maria; Mechsner, Sylvia (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Establishing the diagnostic and surgical management of the inguinal Endometriosis, with further investigation of the biological character.The imaging findings of CT and PET-CT, biopsy, ultrasound, open surgery of the inguinal region with intraoperative cryosection, confirmation and evaluation of tissue infiltration by endometriosis, laparoscopic removal of all endometriotic lesions, reconstruction of the groin. Based on the history of the 29-year-old patient, suffering from a painful growing induration of the inguinal region. Immunohistochemistry performed, in order to analyze the character of the inguinal endometriosis.CT, PET-CT and biopsy did not confirm the diagnosis of endometriosis. Considering, the progressive symptoms of the patient, was performed the surgical intervention. Open surgery of the inguinal region, with a preparation and separation of the groin fibrotic mass lead to the finding of an affected extra-peritoneal portion of the round ligament. Intraoperative cryosection confirmed endometriosis. Simultaneous laparoscopy showed peritoneal endometriosis (rASRM I) and an alteration of the inner round ligament, involving the inner inguinal channel in this process. All endometriotic lesions were removed and the inguinal region reconstructed. The immunohistochemical staining gave evidence of the endometriotic tissue, surrounded by smooth muscle metaplasia.We consider that, reporting this rare case of endometriosis, based on a case report and a literature review, affecting intra and extra peritoneal portion of the round ligament, is an important aid to avoid a wrong diagnosis and method of therapy in future. Our data demonstrated the fully recovery of the patient, after surgical treatment, reporting symptom-free status.